Blocking the entrance of AMP pocket results in hormetic stimulation of imidazolium-based ionic liquids to firefly luciferase. (August 2015) - Chen, Fu; Liu, Shu-Shen; Yu, Mo; Qu, Rui; Wang, Meng-Chao
Graphical abstract: Highlights: [C8 mim]Cl among six ionic liquids has the maximum stimulation effect to luciferase. [C8 mim]Cl and [C10 mim]Cl are competitive inhibitors with both ATP and luciferin. [C8 mim] and [C10 mim] block the entrance of AMP pocket by imidazolium ring. Occupying the AMP site is the main reason for hormetic stimulation by ionic liquid. Abstract: The hormesis characterized by low-concentration stimulation and high-concentration inhibition has gained significant interest over the past decades. Some organic solvents and ionic liquids (ILs) have hormetic concentration responses (HCR) to bioluminescence such as firefly luciferase and Vibrio qinghaiensis sp.-Q67. In this study, we determine the effects of 1-alkyl-3-methylimidazolium chlorine ILs ([C n mim]Cl, n = 2, 4, 6, 8, 10 and 12) to firefly luciferase in order to verify the mechanism of hormesis. The luminescence inhibition toxicity tests show that the stimulation effects of [C8 mim]Cl and [C10 mim]Cl are obvious, [C6 mim]Cl and [C12 mim]Cl are minor, and [C2 mim]Cl and [C4 mim]Cl are rare. The enzyme kinetics show that [C8 mim]Cl and [C10 mim]Cl are the competitive inhibitors with ATP while [C2 mim]Cl and [C4 mim]Cl are the noncompetitive ones. Molecular dynamics simulation results reveal that imidazolium rings of [C8 mim] and [C10 mim] locate at the entrance of luciferin pocket which is adjacent to AMP pocket, while alkyl-chains insert into the bottom of the luciferin pocket. Combining the results from inhibition test, kinetics assay and molecular simulation, we can deduce that occupying AMP pocket by imidazolium ring is responsible for hormetic stimulation.